Investigation of environmentally friendly gypsum based composites with improved water resistance. (10th October 2022) - Doleželová, Magdaléna; Krejsová, Jitka; Scheinherrová, Lenka; Keppert, Martin; Vimmrová, Alena
Abstract: The water resistance of gypsum based composites, prepared from composed binder and silica sand was investigated. The composed binder contained hemihydrate gypsum, lime hydrate and several supplementary cementitious materials (SCM). Silica fume, granulated blast slag and waste ceramic dust were used as SCM in order to compare materials of various origins with different pozzolan activity. Hydrated lime served as an activator of pozzolanic reaction. Gypsum mortar, containing only calcined gypsum and sand was prepared as a reference material. Phase composition, microstructure, mechanical properties and water transport parameters were studied. While the strength of gypsum mortar stored in the water decreased by 90% at the age of one year, the strength of all materials with composed binder increased. The highest strength was achieved by the composite with silica fume, whose compressive strength increased more than three times. The C–S–H phases were found in all materials with SCM and they have finer porous structure than gypsum mortar. Material with silica fume achieved the best combined environmental and functional efficiency. Material with ceramic dust was deeply studied for the first time. This material is most promising because of very good environmental criteria and its price was lowest of all tested materials. The water resistance of gypsum based composites was significantly improved by the addition of SCM. Highlights: Gypsum based composites performed better in water than gypsum mortar. Pozzolanic reaction in gypsum-lime-SCM was confirmed. Environmental impact of gypsum composites was low in comparison with cement or lime. The best functional/environmental efficiency achieved composite with silica fume. Material with ceramic powder is most promising from the economical point of view.